Wear properties of Fe-C-Al cast iron and conventional cast iron - a comparative study - Maleque, Md. Abdul (2011)
The conventional gray cast iron (also known as Fe-C-Si cast iron) exhibitss good properties, such as strength, hardness, corrosion and oxidation resistance but it’s properties especially wear and friction detoriorate significantly at higher temperature. In order to improve the wear properties of this conventional cast iron, an attemped has been made to replace Si by Al. In the present study, the wear test was conducted on both conventional cast iron (CI) and Fe-C-Al cast iron using universal pin-on-disk (POD) machine. The wear track profile and damage surface were characterized using optical profilometer and scanning electron microscopy (SEM) respectively. The results showed that the lower wear rate was found for Fe-C-Al CI compared to conventional Fe-C-Si CI and abrasive type wear morphology was observed in both types of cast iron materials. The results also showed that the friction coeficient value of Fe-C-Al CI was lower than conventional cast iron. It can be concluded that the overall wear and friction properties of Fe-C-Al CI was better than conventional cast iron. Keywords: Sliding; Two-body abrasion; Cast Iron; Surface Analysis; Profilometry